(untitled) (Journal of Economic Research & Business Administration, 2016)
On the modern stage of development of Kazakhstan as the new in dependent state oriented on market relations, making and realization of the investment politics of the state, aimed at providing of high rates of the economy growing and increase of efficiency of economy, becomes main direction of economic reforms. For the decision of these tasks, and also for providing of structural transformations of economy on the basis of the program of actions of government on deepening of reforms and in the conditions of limit nature of internal sourcings an exceptionally important value acquires bringing in of foreign capital in an economy. The invest ment and general contract companies of commercial property market, the question of search of new partners on business, able to supply necessary commodities and services, gets up before that, decide this problem mostly by organization of tender.